Quantitive measurements and modeling of microwave field intensity in the vicinity of cellular mobile network antennas - Jong, Tze Kian. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The increased demand of its capacity in the country led to a significant increase of cellular base transceiver station (BTS) facilities in public neighbourhood. They are generally perceived as hazardous because of the electromagnetic radiation emitted from these facilities. This has raised some concern among the public and researchers of possible adverse health effects to human due to such radiation. This study aims to be present some measurement results and analysis of power density levels near cellular BTS facilities in Kuching and Kota Samarahan Divisions of Sarawak.